Relationships of peak leg power, 1 maximal repetition half back squat, and leg muscle volume to 5-m sprint performance of junior soccer players - Chelly, M. S.; Cherif, N.; Amar, M. B.; Hermassi, S.; Fathloun, M.; Bouhlel, E.; Tabka, Z.; Shephard, R. J. (The Journal of Strength and Conditioning Research, 2010)
Performance over very short distances (1-5 m) is important in soccer. We investigated this in 23 male regional-level soccer players aged 17.2 +/- 0.7 years, filming body markers to determine the average velocity and acceleration over the first step (VS and AS) and the first 5 m (V5, A5). Data were related to scores on a force-velocity test, squat jump (SJ), countermovement jump (CMJ), and 1 maximal repetition (1 RM) half back squat. Leg and thigh muscle volumes were also assessed anthropometrically. V5 was positively correlated with leg and thigh muscle volumes (r = 0.61, p < 0.05; r = 0.43, p < 0.05, respectively), SJ power (absolute and relative to body mass, r = 0.45, p < 0.05; r = 0.43, p < 0.05, respectively), absolute force-velocity leg power (r = 0.49, p < 0.05), and 1 RM half back squat (r = 0.66, p < 0.001). The use of dimensional exponents did not change coefficients materially. VS was also correlated with leg muscle volume and 1 RM back half squat (r = 0.56, p < 0.01; r = 0.58, p < 0.01, respectively) and more weakly with force-velocity leg power and SJ force (r = 0.49, p < 0.05; r = 0.46, p < 0.5, respectively). However, the CMJ was unrelated to velocity or acceleration. Sprinting ability is correlated with measures of power and force such as the force-velocity test, SJ, and 1 RM half back squat; such measures thus offer useful guidance to soccer coaches who wish to improve the short-distance velocity of their players.